PERANCANGAN LAYANAN DIGITAL BERBASIS WEBSITE PADA PLN ULP AMPERA PALEMBANG DENGAN PENDEKATAN USER-CENTERED DESIGN - Yora Veronica Ananda; Irfan Dwi Jaya (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This internship was conducted at PT PLN (Persero) ULP Ampera Palembang due to the suboptimal customer service and complaint handling process, which resulted in delays and a lack of information transparency. These conditions indicate the need for an information system that can support customer services in a more effective, structured, and user-friendly manner. The purpose of this internship was to analyze and design a web-based customer service information system using the User-Centered Design (UCD) approach. The UCD method was applied by focusing on users as the central element in the system design process. The stages included understanding the context of use, specifying user requirements, designing solutions, and conducting evaluations. Data were collected through direct observation, interviews with relevant stakeholders, and literature studies. The result of this internship is a design of a customer service information system that includes complaint submission features, complaint status tracking, and report management by administrators. The proposed system is expected to improve service effectiveness, accelerate complaint handling, and provide convenience and transparency for customers. In conclusion, the UCD approach is effective in producing a system design that meets user needs and supports improved customer service quality.